The attitude of contemporary Iranian directors and screenwriters toward patients with mental disorders in comparison with general population - Kiandokht Kamalinejad; Seved Vahid Shariat; Negin Eissazade; Mohammadreza Shalbafan (BMC Psychology, 2024)
Abstract Background Mental disorders are accountable for 16% of global disability-adjusted life years (DALYs). Therefore, accessible, cost-effective interventions are needed to help provide preventive and therapeutic options. As directors and screenwriters can reach a great audience, they can use their platform to either promote stigma or educate the public with the correct definition and conception of mental disorders. Therefore, we aimed to measure the stigmatizing attitude of contemporary Iranian directors and screenwriters toward patients with mental disorders in comparison with a general population group. Methods In this comparative study, we included 72 directors and screenwriters between 18 and 65 years of age with a minimum involvement in at least one movie/television show, and 72 age and educationmatched controls. We collected the demographic data of the participants, and used the Persian version of the Level of Contact Report (LCR) to measure their familiarity with mental disorders, and used the Persian version of Social Distance Scale (SDS) and Dangerousness Scale (DS) to measure their attitude toward them. Results Compared to the general population group, directors and screenwriters had significantly lower SDS (12.51 ± 3.8 vs. 13.65 ± 3.73) and DS (12.51 ± 3.8 vs. 13.65 ± 3.73) scores (P < 0.001), indicating a more positive attitude toward patients with mental disorders. Familiarity with mental disorders was not significantly different between the groups. Female sex was associated with a more negative attitude among the directors and screenwriters group. Additionally, among the SDS items, ‘How would you feel about someone with severe mental disorder marrying your children?’ and ‘How would you feel about someone with severe mental disorder taking care of your children for a couple of hours?’ received the most negative feedback in both groups. And among the DS items, ‘there should be a law forbidding a former mental patient the right to obtain a hunting license’ received the most negative feedback in both groups. Conclusions Iranian contemporary directors and screenwriters had a more positive attitude toward patients with mental disorders, compared to general population. Due to this relatively positive attitude, this group of artists can potentially contribute to anti-stigma initiatives by offering educational materials and resources, promoting mental health care, and improving access to mental health care.